TINJAUAN PERHITUNGAN RAB PEMBANGUNAN GEDUNG BERDASARKAN PERMEN PUPR NO. 1 TAHUN 2022 (Pada Pembangunan Ruang Kelas Baru Madrasa Tsanawiya Negeri 6 Maluku Tengah) - Patty, Marvin Patrick; Frans, Pieter Lourens; Gaspersz, Willem (Menara: Jurnal Teknik Sipil, 2024)
ABSTRACT Cost budget plan is a careful cost budget planning needed in the implementation of the construction of a project that contains budget details in the form of workers' wages, material costs and tools to be used. The Ministry of Public Works issued an Analysis of the Unit Price of Work in 2016 and updated with the Analysis of the Unit Price of Work 2022 issued on January 5, 2022 through Public Works and Public Housing Regulation number 1 of 2022. In the new classroom construction project, MTS N 6 Central Maluku uses the calculation of the project cost budget according to Unit Price Analysis of Work Minister of Public Works and Public Housing number 28/PRT/2016, this is because planning was carried out before the issuance of Unit Price Analysis of Work 2022. With the Unit Price Analysis of Work update in 2022, the author will use Public Works and Public Housing Regulation number 1 of 2022 as a basis for review to analyze the Cost Budget Plan for the MTS N 6 Central Maluku project. Keywords: Cost Budget Plan, Unit Price Analysis of Work, Public Works and Public Housing Regulation number 1 of 2022